Embalagem multi-propósito para transporte e promoção de livros - Saito, Felipe Kendy (2013)
When Estúdio LoboLimão printed its first publication, in 2012, a new activity became a part in its schedule, now the team must be present in Comic Books fairs and festivals. In these occasions it was noticed the necessity of improvement of the methods of transportation and promotion of the products and the brand. The project of a display starts and three models were developed. The first one was a permanent display, the second was a portable kind of display and the last one is a package box that turns into a display for books. To analyze the properties and the viability of the models prototypes were built and manipulated. Due to the properties like versatility and resistance of the paperboard it was used as principal component to build the models.